The Chilean Child: Aspects of the Making of Emotional Regimes through a School Textbook (1933-1967) - Toro Blanco, Pablo Andrés (Historia y Memoria de la Educación, 2015)
An accelerated expansion of school enrollment in Chile resulted in the production and circulation of reading texts thought to be suitable and edifying for young students, promoting a dynamic publishing industry. In 1933, educator and writer César Bunster, responding to that demand, published an auxiliary book of readings entitled El Niño Chileno (The Chilean Child), subject of numerous reprints and reissues, becoming a reference point for the formation of several generations of Chileans. Bunster’ book, a sort of anthology of authors of universal as well as Latin American and Chilean literature, was meant to portray a desirable profile of a student. After the success of the first editions of the work, this profile would differ by gender. This article seeks to identify, characterize and analyze some emotional topics in the selection of texts from this publication, appreciating changes and continuities over more than three decades. It enables to discern the way in which communities, groups or formal structures - such as the state - promote or discourage certain emotions, thus exercising a kind of regulatory framework, one which Peter and Carol Stearns characterized as «emocionologies». More recently, and in a more critical perspective, William Reddy has described this as the work of «emotional regimes». In frameworks such as the school system, the induction of specific emotions (or the neglect of others) would operate, inter alia, through texts used as a complement to the curriculum.